A Piagetian programme of intervention: facilitation of conceptual change and cognitive growth - Moore, Robert Soulsby (Rhodes University, Faculty of Humanities, Department of Psychology, 1981)
This research aims (within a strictly Piagetian framework) toward the development of a programme of intervention which will facilitate cognitive development, conceptual change and scientific literacy for those individuals who experience difficulty in coping with contemporary scientific and technological concepts. The research focuses specifically on the development of a diagnostic battery useful for realising a conceptual profile of the individual. This profile would indicate personal areas of functional interests that can be used creatively as a starting point for the facilitation of cognitive growth. The goal of such a programme is not the acceleration of cognitive growth, but rather the restoration of the individual to the mainstream of transactions in which the process of growth can flourish. The proposed facilitatory programme makes use of Piagetian tasks in a voluntary, individualist mode of instruction comparable to recently developed techniques of scientific education programmes. In brief, this research analyses three specific areas: 1) The development of a body of theory that can assist in the development of such a facilitatory programme, 2) The development of a diagnostic battery to provide insight into the individual's level of conceptual development, 3) The realization of certain guidelines for an instructional procedure whereby facilitation of growth can begin . The experiment takes the form of a pilot study of twenty four black and white subjects, exploring whether the battery of Piagetian tasks reveals a profile of conceptual development of the individual. Unique conceptual profiles were realized for all individuals, with evidence pointing towards the existence of a relationship between functional interests and the more advanced areas of the individual's conceptual development.
Keywords: Uncatalogued